Green synthesized silver nanoparticles for cream formulation: its anti-inflammatory and healing activities. Issue 1 (March 2020) - Adeleye, OA; Badru, AO; Oyinloye, OE; Fagbohun, AB; Bakre, LG; Bamiro, OA; Babalola, CO; Lateef, A
Abstract: Among several forms of metallic nanoparticles used in biomedical applications, AgNPs are the most fascinating and widely used. Therefore, this study was carried out to evaluate the antiinflammatory activity of Ehretia cymosa -AgNPs cream. Different extracts of the plant (methanol, ME; n-hexane, NE; ethylacetate, EE) were used to synthesize AgNPs, which were characterized by UV and FTIR spectroscopy. The AgNPs were used to prepare creams, and the physical properties of the creams were evaluated. Anti-inflammatory activities of the creams were evaluated by carrageenan induced rat paw edema method on albino rats. The biosynthesized AgNPs had UV absorption spectra in the range 400-450 nm. The creams had pH of 4.6-5.6 similar to the pH of the skin. Cream formulation NO (no extract) had no significant anti-inflammatory activity within 6 h of treatment while formulations NE, ME and EE had a significant anti-inflammatory activity within 6 h of treatment. The efficacy of the cream formulation of the extracts after 6 h of treatment was in the order EE > ME > NE. There was a significant anti-inflammatory activity with the AgNPs cream formulations. Formulations MS, NS and ES had 87.1, 90 and 100% anti-inflammatory activity, respectively in 4 h of treatment. The ES, MS and NS cream formulations had 100% healing in 4, 5 and 6 h, respectively, while only formulation EE had 100% healing in 6 h. Other cream formulations containing the extract could not achieve 100% healing in 6 h. The study established that Ehretia cymosa -synthesized AgNPs cream formulations had a faster healing ability compared with the positive control and Ehretia cymosa cream formulations.